Residues in the GluN1 C-terminal Domain Control Kinetics and Pharmacology of GluN1/GluN3A N-methyl-D-aspartate Receptors - Cummings, Kirstie A. (Neuropharmacology, 2017)
N-methyl-D-aspartate (NMDA) receptors assembled from GluN1 and GluN3 subunits are unique in that they form glycine-gated excitatory channels that are insensitive to glutamate and NMDA. Alternative splicing of the GluN1 subunit mRNA results in eight variants with regulated expression patterns and post translational modifications. Here we investigate the role of residues in the GluN1 C-terminal splicing in receptor gating and modulation. We measured whole-cell currents from recombinant GluN1/GluN3A receptors expressed in HEK293 cells that differed in the sequence of their GluN1 C-terminal tail. We found that these residues controlled the level of steady-state activity and the degree to which activity was facilitated by zinc and protons. Further, we found that the phosphorylation status of sites specific to certain variants can also modulate channel activity. Based on these resutl we suggest that GluN1 C-terminal domain splicing may confer cell-specific and activity-dependent regulation onto the level and pharmacologic sensitivity of GluN1/GluN3A currents.